LongShengZhi Capsule Attenuates Alzheimer-Like Pathology in APP/PS1 Double Transgenic Mice by Reducing Neuronal Oxidative Stress and Inflammation - Yin, Zequn; Wang, Xuerui; Zheng, Shihong; Cao, Peichang; Chen, Yuanli; Yu, Maoyun; Liao, Chenzhong; Zhang, Zhongyuan; Han, Jihong; Duan, Yajun; Yang, Xiaoxiao; Zhang, Shuang (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is the most common form of dementia in the elderly. It may be caused by oxidative stress, inflammation, and cerebrovascular dysfunctions in the brain. LongShengZhi Capsule (LSZ), a traditional Chinese medicine, has been approved by the China Food and Drug Administration for treatment of patients with cardiovascular/cerebrovascular disease. LSZ contains several neuroprotective ingredients, including Hirudo, Astmgali Radix, Carthami Flos (Honghua), Persicae Semen (Taoren), Acori Tatarinowii Rhizoma (Shichangpu), and Acanthopanax Senticosus (Ciwujia). In this study, we aimed to determine the effect of LSZ on the AD process. Double transgenic mice expressing the amyloid-β precursor protein and mutant human presenilin 1 (APP/PS1) to model AD were treated with LSZ for 7 months starting at 2 months of age. LSZ significantly improved the cognition of the mice without adverse effects, indicating its high degree of safety and efficacy after a long-term treatment. LSZ reduced AD biomarker Aβ plaque accumulation by inhibiting β-secretase and γ-secretase gene expression. LSZ also reduced p-Tau expression, cell death, and inflammation in the brain. Consistently, in vitro, LSZ ethanol extract enhanced neuronal viability by reducing L-glutamic acid-induced oxidative stress and inflammation in HT-22 cells. LSZ exerted antioxidative effects by enhancing superoxide dismutase and glutathione peroxidase expression, reduced Aβ accumulation by inhibiting β-secretase and γ-secretase mRNA expression, and decreased p-Tau level by inhibiting NF-κB-mediated inflammation. It also demonstrated neuroprotective effects by regulating the Fas cell surface death receptor/B-cell lymphoma 2/p53 pathway. Taken together, our study demonstrates the antioxidative stress, anti-inflammatory, and neuroprotective effects of LSZ in the AD-like pathological process and suggests it could be a potential medicine for AD treatment.